(untitled) (Revista Apotheke, 2022)
There is in current generations what has been called "nature deficit" due to lack of contact with natural environments. Linked to this, we find concepts such as "naturalistic intelligence" and "natural heritage". The aim of this paper is to analyze the implications that the family has in the education of their children and as an active part of the educational system in the awareness of natural heritage and the environment. Based on Arts-Based Educational Research and Walking pedagogy, heritage education and visual autoethnography, we present different experiences that raise awareness of the value that the family acquires in natural heritage education and in what Michel Serres called the "natural contract": a commitment that we must all subscribe to at birth with the planet we inhabit. These family experiences for natural heritage education are undertaken from the researcher’s double condition of being a parent and art educator in a Faculty of Education, and of having the responsibility of educating future teachers to work with their students on respect for the environment, appreciation for natural spaces or natural heritage.